Quality seed in SAARC countries : production, processing, legal and quality control, and marketing system - Huda, Md. Nazmul; Saiyed, Ibrahim Md.; SAARC Agricultural Information Centre (Dhaka : SAARC Agriculture Centre, 2011)
Compendium of the country papers presented at the Regional Workshop on "Quality Seed in SAARC Countries: Production, Processing, Legal and Quality Control, and Marketing System", held in New Delhi, India, in Dec. 16-18, 2009.
Includes bibliographical references.
Keywords: Seeds -- Quality -- South Asia -- Congresses